Adapting the protocol for studying the functional capacity of T lymphocytes thawed from cryopreservation - E. V. Saidakova; L. B. Korolevskaya; V. N. Ponomareva; V. V. Vlasova (Acta Biomedica Scientifica, 2024)
Background. Immunological studies are impossible without long-term storage of cryopreserved biomaterial. There are no standard procedures for working with cryopreserved mononuclear leukocytes.The aim of the study. To optimize the protocol for culturing T lymphocytes thawed after cryopreservation by assessing their viability and proliferative capacity.Methods. Mononuclear leukocytes were isolated from the peripheral blood of relatively healthy volunteers (n = 18). Cells were subjected to controlled freezing down to –80 °C and were transferred to liquid nitrogen. First step: after thawing, the cells were stained with CFSE (carboxyfluorescein succinimidyl ester), were divided into two parts and cultured in the presence/absence of interleukin 2 (IL-2). Cell proliferation was stimulated with phytohemagglutinin (type P). Cells were incubated for 7 days. Sample analysis was performed using flow cytometry. Second stage: thawed cells were divided into three parts. Two parts were resuspended in a full growth medium with IL-2 and were placed in a thermostat (+37 °C) to “rest” for one hour or overnight. After “resting”, the cells were stained with CFSE. One third of the thawed leukocytes were stained with CFSE immediately after thawing. Cells were stimulated, cultured and analyzed the same way at both stages of the study.Results. It has been established that adding IL-2 to the culture medium contributes to a better cell survival. In the presence of IL-2, stimulated CD4+ and CD8+ T lymphocytes produced more daughter cell generations. At the end of the 7-day incubation “rested” samples had reduced leukocyte counts compared to the samples that were cultured immediately after thawing. The number of daughter cell generations formed by stimulated CD4+ and CD8+ T cells decreased when the “rest” stage was included into the study protocol.Conclusion. Adding IL-2 into culture medium can increase the viability and mitotic capacity of thawed T cells, making their state more similar to that of freshly isolated lymphocytes. Cell “rest” after thawing negatively affects the viability and proliferative activity of T lymphocytes during their weekly incubation.